The “Italian hebrid”, Hebrus franzi (Wagner, 1957): disentangling a half-century dilemma (Hemiptera: Heteroptera: Gerromorpha) - Cianferoni, Fabio; Buzzetti, Filippo Maria; Zettel, Herbert (Zootaxa, 2016)
Hebrus franzi (Wagner, 1957) was described from the Apuan Alps (Tuscany, Italy) and not found again for several decades despite intensive search. We report on new collections that expand the known distribution area considerably, provide a redescription, and give first insights regarding the ecology of this remarkable flightless species.